The Effect of ESG Score and Foreign Ownership on Financial Reporting Delay, with Financial Distress Measured Using The Merton Model as A Mediating Variable: A Study of Manufacturing Companies on The IDX from 2020 to 2024 - Steven Liong Winoto; Oktavia; Soegeng Wahyoedi (Journal of Economics and Business UBS, 2026)
This study aims to examine the effect of ESG score and foreign ownership on financial reporting delay with financial distress as a mediation variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The population comprises all manufacturing companies listed on the IDX. Purposive sampling method resulted in 23 companies with 115 annual observations. Data analysis employed panel data regression using the Two-Stage Least Squares (TSLS) method to address endogeneity issues. Model selection was conducted through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results indicate that Equation 1 uses the Common Effect Model (CEM), while Equations 2 and 3 use the Fixed Effect Model (FEM). The findings reveal that ESG score has no significant effect on financial distress (p = 0.293 > 0.05) nor on financial reporting delay (p = 0.747 > 0.05). Foreign ownership has no significant effect on financial distress (p = 0.280 > 0.05). Financial distress has no significant effect on financial reporting delay (p = 0.348 > 0.05). Furthermore, financial distress does not mediate the effect of ESG score nor foreign ownership on financial reporting delay. Consequently, all five hypotheses are rejected. The implication is that ESG has not yet become a sufficiently strong factor in influencing corporate financial health in Indonesia. The novelty of this study lies in the use of the Merton Model to measure financial distress and the TSLS method to address endogeneity in the mediation model within the context of Indonesian manufacturing companies.